2000
DOI: 10.1152/jn.2000.83.2.766
|View full text |Cite
|
Sign up to set email alerts
|

Prototypical Imidazoline-1 Receptor Ligand Moxonidine Activates Alpha2-Adrenoceptors in Bulbospinal Neurons of the RVL

Abstract: Hayar, Abdallah and Patrice G. Guyenet. Prototypical imidazoline-1 receptor ligand moxonidine activates alpha2-adrenoceptors in bulbospinal neurons of the RVL. J. Neurophysiol. 83: 766 -776, 2000. Moxonidine is an antihypertensive drug that lowers sympathetic vasomotor tone by stimulating either alpha2-adrenergic (␣2-AR) or imidazoline I1 receptors within the rostral ventrolateral medulla (RVL). In this study, we investigated the effects of moxonidine (10 M) on RVL neurons in brain stem slices of neonatal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
3
3
0
1
Order By: Relevance
“…The significant SKF 86466 pretreatment × time interaction effect with the preserved but smaller initial increase in blood pressure in our study suggests that the α 2 ‐antagonist may counteract the clonidine‐evoked hypotension. While this observation is consistent with the study in humans by Hayar & Guyenet (2000), the trend for a hypotensive effect of SKF 86466 ( P = 0.07) in our study does not permit unequivocal acceptance of this interpretation.…”
Section: Discussionsupporting
confidence: 71%
“…The significant SKF 86466 pretreatment × time interaction effect with the preserved but smaller initial increase in blood pressure in our study suggests that the α 2 ‐antagonist may counteract the clonidine‐evoked hypotension. While this observation is consistent with the study in humans by Hayar & Guyenet (2000), the trend for a hypotensive effect of SKF 86466 ( P = 0.07) in our study does not permit unequivocal acceptance of this interpretation.…”
Section: Discussionsupporting
confidence: 71%
“…These results are in agreement with previous studies performed in brain stem slices of neonatal rats [30]. Nevertheless, in that study the authors used either an extracellular recording technique or a whole cell recording technique to study putative premotor sympathetic neurons which were identified mainly as retrogradely labeled RVLM bulbospinal neurons [30]. In our present study putative premotor sympathetic neurons were identified by their electrophysiological characteristics, as described in previous publications [13,25].…”
Section: Granatasupporting
confidence: 93%
“…However, this hypothesis is not supported by the experiments reported by Hayar and Guyenet [30] showing that: (1) moxonidine, at concentrations similar to those used in the present study, produced a consistent inhibitory effect on different types of RVLM neurons recorded in an in vitro slice preparation, and this effect is due in part to postsynaptic hyperpolarization; (2) the inhibitory effects of moxonidine were substantially blocked by the selective antagonist of · 2 -adrenergic receptors SKF 86466, while on the other hand, the imidazoline type-1 antagonist AGN 192403 was ineffective in changing neuronal activity, and (3) the inhibitory effects of moxonidine characterized at pre-and postsynaptic levels are similar to those generated by norepinephrine and other · 2 -adrenergic agonists on putative presympathetic RVLM neurons. Similar results were reported by Szabo et al [31] in experiments performed on the rat locus coeruleus neurons in vitro.…”
Section: Granatamentioning
confidence: 66%
“…Nevertheless, its weak affinity for ␣2-adrenergic receptors (Ferry et al, 1988;Ernsberger et al, 1993) may have accounted for the observed inhibition of IPSCs. Hayar and Guyenet (2000) revealed that inhibition of both EPSCs and IPSCs by moxonidine in bulbospinal neurons of the rostral ventrolateral medulla is mediated via ␣2-adrenergic receptors. Indeed, in the present study, application of noradrenaline under blockade of both ␣1-and ␤-adrenergic receptors with prazosin and propranolol, respectively, resulted in ␣2-adrenergic receptor-mediated inhibition of IPSCs, as was demonstrated by the apparent lack of inhibition by noradrenaline when combined with either yohimbine or SKF86466, which are non-imidazoline antagonists selective for ␣2-adrenergic receptors.…”
Section: -Imidazoline Receptors Mediate Moxonidine-induced Inhibimentioning
confidence: 99%